Sequências de ensino investigativas: o que dizem as pesquisas da última década - Nascimento, Sebastião Pereira do (Brasil, 2025)
Inquiry-based teaching has emerged as an important tool, encompassing projects aimed at achieving Scientific Literacy. The theoretical foundations underpinning this methodology in education are constructivist perspectives, specifically rooted in the theories of Piaget and Vygotsky. Our research aims to understand how studies on Investigative Teaching Sequences, in recent years (2013-2020), have contributed to Physics education. To address this objective, we employed a qualitative approach methodology characterized by systematic literature analysis. Discursive Textual Analysis was used as the methodological procedure for information analysis. We utilized the CAPES Periodicals Portal to gather works addressing the theme of Inquiry-based Teaching in recent years. For analysis of the selected works, we defined the following categories: a) Journals and their classification in the qualis system; b) Educational levels addressed in the selected works; c) Geographical location of authors' institutions; d) Physics areas covered in the works; e) Environment in which the activity was proposed/conducted. Results indicate a predominance of publications in qualis A journals. The classroom was the most common environment for proposal development, with a prevalence of research focusing on mechanics in high school education. Geographically, there was a good distribution across all regions of Brazil.